Vingt ans de droits des détenus au Québec - Lemire, Guy (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1991)
Discussion of prisoners' rights has often been the centre of attention over the past twenty years or so. While it can help in denouncing the abuse of authority, it is a different matter when it is a question of analyzing the violence between prisoners that is one of the major characteristics of the prison today. It has tended to take refuge in a legalism that leaves no room for more concrete human considerations. By rallying the abolitionists, it has helped to discredit the reeducational prisons that in the sixties were trying to give the prison milieu a more humane image. The outcome is very uncertain.